Evaluation of radio-wave method of soil massif - A.M. Kudelya (Геофизический журнал, 2014)
Analysis of theoretical results given in the paper of S. T. Maklovich and Yu. N. Kozulin "On energy propagation of electromagnetic field from dipole source in presence of conducting halfspace" has been proposed. On the base of an assumption of similarity of electromagnetic field distribution of oscillating vertical and horizontal magnetic dipole in presence of conducting half-space, experimental studies of soil massif with known media interface have been conducted. Results of experimental studies of soil massif by crossed magnetic dipoles have been compared with theoretical calculations and valuation of geometric sounding by radio-wave method has been done.